The challenges of mental health in Chilean university students - Beroíza-Valenzuela, Francisca (Frontiers in Public Health, 2024)
Mental health is a crucial issue in Chile and worldwide, gaining even more relevance following social events in Chile in 2019, including the sociopolitical crisis and the COVID-19 pandemic. In Chile, over 20% of adolescents experience mental health problems such as anxiety, depression, and stress, with many going untreated due to limited access or the stigma associated with these issues. The COVID-19 pandemic has exacerbated this situation, with a 25% increase in the prevalence of anxiety and depression. The university population is particularly vulnerable to mental health challenges due to the unique pressures of the academic environment, including increased academic demands and the acquisition of university-related behaviors that can negatively impact physical and mental health, with notable gender differences. Effectively addressing these issues is essential for ensuring the emotional and psychological well-being of university students. Specific policies and programs are needed to address the mental health needs of university adolescents and ensure that they have access to mental health services required to navigate the challenges of daily life. A methodology reflective of the essayistic approach guides this exploration, which is characterized by critical reflection and structured argumentation.